Thriving of employees with disabilities: The roles of job self‐efficacy, inclusion, and team‐learning climate - Zhu, Xiji; Law, Kenneth S.; Sun, Cong (Timothy); Yang, Dan (Human resource management, 2019)
With the growing global emphasis on welfare‐to‐work policies, an increasing number of people with disabilities (PWD) have entered the workforce. However, studies on PWD have focused primarily on company practices to accommodate PWD, with a limited understanding of factors affecting psychological integration of PWD into the workplace. This scarcity in research makes it difficult for managers to utilize the full work potential of PWD. To fill this research gap, the current study focuses on the job self‐efficacy of PWD and investigates how employee disability interacts with inclusion and team‐learning climate to affect job self‐efficacy, and in turn thriving at work. Using a sample of 485 employees in 114 teams, surveys found job self‐efficacy was a key intervening mechanism linking employee disability to thriving at work. These results suggest high workplace inclusion can buffer potential negative effects of disability at the individual level, strengthened further by a high team‐learning climate. The data supported a three‐way cross‐level interaction effect of disability, inclusion, and team‐learning climate on the thriving of employees with disabilities, through job self‐efficacy. Our results demonstrate the importance of inclusion and team‐learning climate to foster employee thriving in a diverse workforce.